Directed reading activities with explicit writing instruction and student reading comprehension, writing ability, reading attitude, and writing attitude - Galicia, Michelly P. (College of Education, University of the Philippines Diliman, 2014)
Reading and writing are important life skills which student must master in order to become successful educationally, occupationally, and socially (Graham & Herbert, 2011: 710). Promotion of reading and writing attitude is also important because of its influence on the behavior of students (Schumm, 2006; McKenna, 1995). Given the importance of reading and writing in the intermediate grades, this multiple case study with correlations used a single pretest-posttest design to investigate the effects of Directed Reading Activities with Explicit Writing Instruction on the reading comprehension, writing ability, reading attitude, and writing attitude of 12 case study students. Directed Reading Activities (DRA) provides students with instructional support before, during, and after reading (Betts, 1946). On the other hand, Explicit Writing Instruction (EWI) is a consequence of instructional support in writing that involves explanation, demonstration, and practice (Belchenko, 2010). In addition, the study also determined whether or not there is a relationship between the dependent variables, namely reading comprehension, writing ability, reading attitude, and writing attitude. The participants were 12 incoming grades five and six students, aged 9-12, from public schools in Quezon City. Pre- and post-intervention assessment were given using the following instruments1) Draft Philippine Informal Reading Inventory (Phil-IRI) 2013 in Filipino IV to measure reading comprehension, (2) Descriptive writing test to evaluate writing ability using the 6 + 1 Traits Writing Rubric, (3) Reading Attitude Scale (RAS) to measure reading attitude, and (4) Writing Attitude Survey (WAS) to measure writing attitude. After 21 sessions of intervention, the pretest and posttest scores of the case study students in the aforementioned instrument as well as their scores in the Directed Reading Activities Post Lesson Assessments (DRA PLAs) and Explicit Writing Instruction Post Lesson Assessment (EWI PLAs) were analysed. The results of the study showed that all 12 case study students, regardless of their baseline skills, improved in their writing ability after exposure to the intervention. Meanwhile, analysis of the draft Phil-IRI scores showed the lack of positive effect on the reading comprehension of students, although results of the DRA PLAs indicated otherwise. The students scores on the RAS and WAS revealed a light decrease from pretest to posttest, although their reading attitude and writing attitude remained positive and fairly unchanged after the intervention. The result of the Spearmans coefficient of rank correlation showed the absence of correlation between the following: Reading Comprehension (RC) and Writing Ability (WAb), Reading Comprehension (RC) and Reading Attitude (Rat), Reading Comprehension (RC) and Writing Attitude (WAt), Writing Ability (WAb) and Writing Attitude (WAt), Writing Ability (WAt) and Reading Attitude (Rat). Based on the result of the study, the following recommendations are set: (1) Teachers should provide explicit instruction not just in writing but also in reading to enhance the reading and writing skills as well as the reading and writing attitude of students, (2) School administrators should encourage the use of Directed Reading Activities and Explicit Writing Instruction and alternative assessment tools in their classrooms, (3) Future studies should replicate the intervention with a larger sample using multiple assessment tools over an extended period of time.